Some Results on Perturbation of Duality of OPV-Frames - Sharma, Raksha (Armenian Journal of Mathematics, 2024)
In this paper, we consider a perturbation of operator-valued frames (OPV-frames) and obtain conditions for their stability in terms of operators associated with the OPV-frames. Also, some duality relations of OPV-frames are discussed. Finally, some properties of the duals of OPV-frames are proven.